The Chinese healthcare challenge: Comment on "Shanghai rising: avoidable mortality as measured by avoidable mortality since 2000" - Fabre, Guilhem (Int J Health Policy Manag, 2015)
Investments in the extension of health insurance coverage, the strengthening of public health services, as well as primary care and better hospitals, highlights the emerging role of healthcare as part of China’s new growth regime, based on an expansion of services, and redistributive policies. Such investments, apart from their central role in terms of relief for low-income people, serve to rebalance the Chinese economy away from export-led growth toward the domestic market, particularly in megacity-regions as Shanghai and the Pearl River Delta, which confront the challenge of integrating migrant workers. Based on the paper by Gusmano and colleagues, one would expect improvements in population health for permanent residents of China’s cities. The challenge ahead, however, is how to address the growth of inequalities in income, wealth and the social wage.